PACU JALUR SEBAGAI DAYA TARIK WISATA DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Fauzan Aulia; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purpose to determine Pacu Jalur as a tourist attraction in Kuantan Singingi district Riau Province. This research uses a descriptive quantitative method to study the issue discussed. The sample in this research is 100 respondents which were taken by using accidental sampling. While data collection techniques in this research using observation, questionnaire, and interview by using a likert scale as a measure to determine the length of the short interval. Based on the research that has been done, Pacu Jalur As a Tourist Attractions in Kuantan Singingi District Riau Province are included in the category of strongly agree, because Pacu Jalur is a rare cultural tradition. Keywords : Tourist Attraction, Rare, Tourism, Pacu Jalur, Kuantan Singingi district, Riau Province